The co-existence of Lemierre's syndrome and Bezold's abscesses due to Streptococcus constellatus: A case report. Issue 26 (June 2018) - Yaita, Kenichiro; Sugi, Suzuna; Hayashi, Makiko; Koga, Takuma; Ebata, Tomohiro; Sakai, Yoshiro; Kaieda, Shinjiro; Ida, Hiroaki; Watanabe, Hiroshi
Abstract: Rationale: The ancient infectious diseases, Lemierre's Syndrome and Bezold's Abscesses are rare. Patient concerns: A 70-year-old Japanese woman with a 15-year history of Parkinson's disease was referred to our hospital due to fever, occipital headache and bilateral shoulder pain that had continued for three months. She had been prescribed prednisolone due to a diagnosis of polymyalgia rheumatica. Diagnoses: A blood culture revealed bacteremia of Streptococcus constellatus . In addition, computed tomography revealed Bezold's abscesses and Lemierre's syndrome. Interventions: We administered ceftriaxone for 31 days, followed by oral amoxicillin. Outcomes: The patient recovered and the abscesses improved. Lessons: This case underscores the importance of blood culture tests and cross-referencing with radiological imagings in the diagnoses of these rare critical infectious diseases that mimic polymyalgia rheumatica.